Self‐medication among pregnant women attending outpatients' clinics in northern Jordan‐a cross‐sectional study - Mervat M. Alsous; Sayer I. Al‐Azzam; Mohammad B. Nusair; Saja A. Alnahar; Nail A. Obeidat (Wiley, 2021)
Abstract Self‐medication can facilitate patients' access to medicinal products, save time, and reduce financial and health‐care service use burden. On the other hand, irresponsible use of self‐medications can result in adverse consequences. Self‐medication is common among different demographic groups including pregnant women. In general, medicinal products might have harmful effects on mothers and baby. This study aimed to assess self‐medication practices among pregnant women in the northern region of Jordan. A cross‐sectional study was conducted on pregnant women attending outpatient clinics in the northern region of Jordan. Self‐medication practices among the target population were assessed using a survey questionnaire that was administered through interviewer‐assisted mode. Data were collected between December 2019 and September 2020, and descriptive statistics and inferential analysis were applied. A total of 1,313 pregnant women were surveyed (response rate = 95.50%). Self‐medication and the use of herbal remedies were practiced by 33.10% and 32.14% of the participant, respectively. Headaches and general pains were the most frequently reported conditions treated by self‐medication practice with either conventional medicinal products or herbal remedies. The gravidity (≥4) and the gestational stage (≥28 weeks) were the predictors of self‐medication practice. This study showed that self‐medication was not widely practiced by pregnant women in the northern region of Jordan. Disease simplicity and previous history were the main motives for self‐medicating. Efforts should be made by health‐care providers to address pregnant women and educate them to increase their awareness about the unsafe use of medicines and the harmful effects on fetus.